Starlink Business Model and Network Mode Under the Direct-to-Satellite Service of Mobile Phone - Yuanxing XUE; Zhi ZHAO; Qiaoman DUAN (天地一体化信息网络)
The paper initially provided a brief comparison of the direct-to-satellite solution of three LEO satellite communication companies: Starlink, AST SpaceMobile and Lynk Global.While Starlink has successfully conducted with SMS, Voice and Data service test, AST SpaceMobile and Lynk Global have not made significant progress.Although all are in early stages, their technological paths demonstrate the future trends of direct-to-satellite communication.Focused on Starlink's success, the paper analyzed its business model and explored the primary technological pathways for future integration of space, air and ground telecommunication systems, which was a hot topic in the industry.Based on publicly available information about Starlink, the paper utilized the business model canvas theory to delved into its direct-to-satellite service, detailing aspects like core value, key resources, customer segments, cost structure, customer relations, key partnership, and revenue streams.It then discussed Starlink's network architecture strategies, compared and analyzed the self-built core network and shared core network approaches, ultimately inferring the most viable network technology solution for Starlink.